A Lab-scale HVAC Hissing-type Noise Characterization with Vehicle System Validation - SATAR, Mohd Hafiz Abdul; MAZLAN, Ahmad Zhafran Ahmad; HAMDAN, Muhd Hidayat; ISA, Mohd Syazwan Md; PAIMAN, Muhd Abdul Rahman; GHAPAR, Mohd Zukhairi Abd (Archives of Acoustics, 2021)
Heating, ventilation and air conditional (HVAC) system provides a cold ventilation for the comfort of the driver and passengers in a vehicle. However, the vibration induced by the HVAC contributes to a reasonable level of noise emission, and hissing is one of the critical noises. So far, the characterization of hissing noise from the vehicle is least to be reported compared to other type of noises. Hence, this paper investigates the occurrence of hissing noise from several HVAC components. A lab-scale HVAC system was developed to imitate the real-time operations of the vehicle HVAC system. Two engine conditions, namely as ambient and operating conditions, were tested at speed of 850 rpm and 850–1400 rpm, with the blower speed maintained constantly at one level. The result shows that the hissing noise from the labscale HVAC was produced at frequency range of 4000–6000 Hz. The finding also highlights that the main component contributors of noise emission are an evaporator and a thermal expansion valve. The validation with a real vehicle system showed a good consensus whereby the hissing noise was produced at the similar operating frequency ranges. Also, the hissing noise was found to be louder when in an operating condition which could be taken into consideration by the vehicle manufacturers to improve the HVAC design.